2007
DOI: 10.1111/j.1532-5415.2007.01188.x
|View full text |Cite
|
Sign up to set email alerts
|

Older Age Predicts Short‐Term, Serious Events After Syncope

Abstract: OBJECTIVES: To assess the relationship between age and 14-day serious events after an emergency department (ED) visit for syncope. DESIGN: One-year prospective cohort study. SETTING: Single academic ED. PARTICIPANTS: Adult patients with an ED complaint of syncope or near-syncope. MEASUREMENTS: Treating physicians prospectively recorded the presence or absence of potential risk factors for serious clinical events. Patients were contacted by telephone at 14 days for a structured interview. A three-physician pane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 16 publications
2
21
1
Order By: Relevance
“…For example, we made our estimate for the percentage of patients ≥50 years at intermediate risk based on an analysis of patients ≥60 years of age. 22,36 In addition, the case definition of syncope we used in the NHAMCS contribution to the model may include ED visits where syncope was a secondary complaint. We feel that syncope is a cardinal complaint that often supersedes most associated symptoms in guiding ED management.…”
Section: Limitationsmentioning
confidence: 99%
“…For example, we made our estimate for the percentage of patients ≥50 years at intermediate risk based on an analysis of patients ≥60 years of age. 22,36 In addition, the case definition of syncope we used in the NHAMCS contribution to the model may include ED visits where syncope was a secondary complaint. We feel that syncope is a cardinal complaint that often supersedes most associated symptoms in guiding ED management.…”
Section: Limitationsmentioning
confidence: 99%
“…2 Cardiac and other serious outcomes (adjusted for comorbidity) are also much more common among older patients with syncope (adjusted odds ratio 3.8, 95% confidence interval 1.2-12, for patients over 60 years compared with patients 18-39). 6 This increased risk among older patients is particularly important given the main finding reported by Saccilotto and colleagues, 4 namely that the San Francisco Syncope Rule (Box 1) is the most adequately validated across various populations, 8 a finding echoed in a recent, similar meta-analysis. 9 As the authors point out, al though the San Francisco Syncope Rule can aid decision-making at triage in emergency departments, it should be used only in tandem with a de tailed clinical assessment, particularly in older individuals.…”
mentioning
confidence: 62%
“…Age has been shown to be an important predictor of SAEs. 2,19,[25][26][27] Shortness of breath has been found to be an important variable in both our study and the San Francisco Syncope Rule (SFSR) study, and in our study, it was a marker of underlying life-threatening conditions such as pulmonary embolism or massive pleural effusion. We found that patients with systolic BP , 80 mm Hg during the ED stay typically had ongoing gastrointestinal bleeding or sepsis.…”
Section: Discussionmentioning
confidence: 84%